Digital twin-enabled reconfigurable modeling for smart manufacturing systems. Issue 7 (3rd August 2021) - Zhang, Chenyuan; Xu, Wenjun; Liu, Jiayi; Liu, Zhihao; Zhou, Zude; Pham, Duc Truong
ABSTRACT: The digital twin-based manufacturing system is a typical representative of smart manufacturing and has a number of advantages beyond the state of the art. However, when a manufacturing system needs to be reconfigured to meet new requirements of production, manual reconfiguration is time-consuming and high labor cost because of the complexity of the digital twin-based manufacturing system and the imperfection of related models. This problem will be even worse if there are industrial robots with characteristics of complex functions and inflexible programming in the manufacturing system. This paper presents a five-dimensional fusion model of a digital twin virtual entity for robotics-based smart manufacturing systems to support automatic reconfiguration, which can not only realistically describes physical manufacturing resources, but also represents the capabilities and dependencies of the digital twins. Reconfigurable strategies based on service function blocks, which can improve the reusability of functions and algorithms, are proposed to make the robotics-based manufacturing system satisfy the various reconfigurable requirements of different granularities and goals. Finally, a prototype system is developed to demonstrate the performance of the reconfigurable digital twin-based manufacturing system, which can improve the operation efficiency of such systems for carrying out the reconfiguring production tasks in a flexible way.